Analisis Amilosa, Daya Cerna Pati dan Uji Organoleptik Beras Merah Pratanak dengan Ekstrak Brokoli - Rafika, Muhana; Hidayat, Manarul; Nurlina, Ade (Media Gizi Ilmiah Indonesia, 2025)
Patients with Diabetes Mellitus (DM) are recommended to consume foods with a low glycemic index (GI). Red rice has a lower GI than white rice. The GI value of rice is influenced by amylose and starch content. The higher the amylose content and the lower the digestibility of starch in rice, the lower the GI value. The fiber content of broccoli can slow down the digestibility of starch and glucose response becomes low. The purpose of the study was to determine the amylose content and starch digestibility of pratanak red rice with broccoli extracts. Experimental research methods using sample A (50 grams red rice +2% broccoli extract), sample B (50 grams red rice +10% broccoli extract), and sample C (50 grams red rice +50% broccoli extract). Testing of amylose content and starch digestibility using spectrophotometric method. The results showed that the amylose content of sample A was 7.76%, sample B was 7.26%, and sample C was 6.73%. Starch digestibility in sample A was 3.62%, sample B was 3.93%, and sample C was 4.54%. Organoleptic results showed no significant difference (P ≥0.05). The best formula was sample A based on the assessment of highest amylose content, lower starch digestibility, and the highest organoleptic.